Leadership among education students in Universiti Utara Malaysia: significance of leadership development programmes - Andyson Junis James,; Faisal Zulhumadi,; Nur Marissa Vee, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper investigates the significance of leadership skills development programmes among education students at Universiti Utara Malaysia. Leadership skills are a combination of characteristics that allow individuals to guide, encourage, and motivate others to achieve common goals. The motivation for this study lies in the need for future leaders to be fostered in the education system to lead their teams to give their all. Good leaders would acknowledge and value individual efforts, offer constructive criticism, and promote a happy and encouraging work atmosphere. The main issues addressed in this paper include factors that can be influenced by good development of leadership skills among education students through leadership development programmes. Data were collected through surveys among the students in the School of Education, Universiti Utara Malaysia. The study's results supported that leadership style and ability enhance personal characteristics, social skills, and decision-making ability, all of which are required for effective leadership. This research contributes to the body of knowledge by supporting ethical and moral leadership, knowledge related to preparation for educational leadership roles, and positive impact on students' achievement.